"MODERN ASPECTS OF FORECASTING AND EARLY DIAGNOSIS OF FETAL HYPOXIA TO REDUCE THE PERINATAL INCIDENCE OF HYPOXIC- ISCHEMIC GENESIS" - Boltaeva Malika Miralievna (Academia Science Repository, 2023)
In the modern world, the problem of ischemic and hypoxic brain damage in newborns remains an urgent problem, since intrauterine brain suffering subsequently leads to serious complications leading to an increase in perinatal mortality and disability in children. In children born with ischemic brain lesions, there is a high mortality, and in the structure of early childhood disability, this pathology is 60-70%.